1990
DOI: 10.3147/jsfp.25.93
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory effects of levamisole on rainbow trout, Oncorhynchus mykiss.

Abstract: The immunomodulatory effects of levamisole were investigated using rainbow trout, Oncor hynchus mykiss. Fish sampled 5 days after intraperitoneal injection of levamisole showed in creased protection against Vibrio anguillarum when a single dose (0.5 mg/kg) was used. Phago cytic activity, chemiluminescence responses and natural killer cell activity in fish treated with levamisole were also increased, compared with those in the saline treated fish. Furthermore, levamisole activated the alternative complement pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
1
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(135 citation statements)
references
References 13 publications
5
126
1
3
Order By: Relevance
“…The compound included on pacu diet is a synthetic anthelmintic extensively applied in veterinary and human treatments, and has shown a potent immune modulatory action on innate and acquired immune systems of several species, such as Sparus aurata, Salmo salar, Oncorhynchus mykiss and Cyprinus carpio (Siwicki, 1989;Jeney and Anderson, 1993;Mulero et al, 1998;Findlay and Munday, 2000;Cuesta et al, 2002Cuesta et al, , 2004. Therefore, levamisole has prompt resistance against various etiological agents, such as Vibrio anguillarum, A. hydrophila, Paramoeba sp., Edwardsiella tarda, Photobacterium damselae and nematodes as Anguillicola crassus (Kajita et al, 1990;Geets et al, 1992;Baba et al, 1993;Findlay et al, 2000; Leano et al, 2003;Munday and Zilberg, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The compound included on pacu diet is a synthetic anthelmintic extensively applied in veterinary and human treatments, and has shown a potent immune modulatory action on innate and acquired immune systems of several species, such as Sparus aurata, Salmo salar, Oncorhynchus mykiss and Cyprinus carpio (Siwicki, 1989;Jeney and Anderson, 1993;Mulero et al, 1998;Findlay and Munday, 2000;Cuesta et al, 2002Cuesta et al, , 2004. Therefore, levamisole has prompt resistance against various etiological agents, such as Vibrio anguillarum, A. hydrophila, Paramoeba sp., Edwardsiella tarda, Photobacterium damselae and nematodes as Anguillicola crassus (Kajita et al, 1990;Geets et al, 1992;Baba et al, 1993;Findlay et al, 2000; Leano et al, 2003;Munday and Zilberg, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…have been studied as prospective immunostimulants for fish (reviewed by Sakai [8]), and some have been reported to confer a degree of protection against several diseases commonly found in farmed fishes, caused by Vibrio anguillarum, Aeromonas salmonicida or Yersinia ruckeri, etc. [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in salmonids, such as Salmo salar and Oncorhynchus mykiss, in vivo, it increases immunity (Kajita et al 1990 FIGURA 3. Efecto de diferentes dosis de levamisol (24 h de tratamiento) sobre la producción de óxido nítrico (NO) medido como Nitrito (NO 2 -) por las células mononucleares de sangre periférica de trucha.…”
Section: Discussionunclassified
“…These compounds, being efficient to increase immunocompetency and resistance to infections, have been used in aquaculture, veterinary and human medicine (Sakai 1999). One of these immunostimulating compounds is levamisole (Kajita et al 1990;Findlay & Munday 2000;Ispir & Yonar 2007). It is a synthetic compound originally used as an anti-helminthic livestock and later on its immunostimulating property was demonstrated, leading to its use with this second purpose in veterinary and human medicine (Sakai 1999).…”
Section: Introductionmentioning
confidence: 99%